2007
DOI: 10.1089/tmj.2006.0053
|View full text |Cite
|
Sign up to set email alerts
|

An Internet-Based Interactive Telemonitoring System for Improving Childhood Asthma Outcomes in Taiwan

Abstract: A randomized, controlled trial was conducted to assess the effectiveness of Blue Angel for Asthma Kids, an Internet-based interactive asthma educational and monitoring program, used in the management of asthmatic children. One hundred sixty-four (n = 164) pediatric patients with persistent asthma were enrolled and randomized into two study groups for a 12-week controlled trial. The intervention group had 88 participants who were taught to monitor their peak expiratory flows (PEF) and asthma symptoms daily on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
148
0
11

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(165 citation statements)
references
References 25 publications
6
148
0
11
Order By: Relevance
“…The results of Jan et al 54 are supported by other studies in the field, such as that by Rasmussen et al 55 In this study, it was demonstrated in an RCT of 300 adults with asthma that an IHCA was able to increase the patient's adherence to asthma medication, improve clinical outcomes, and improve the patient's quality of life. 55 Although effect sizes were not reported for this study, it provides supporting evidence concerning the long-term positive effects of IHCAs in the area of patient adherence to medications.…”
supporting
confidence: 74%
See 1 more Smart Citation
“…The results of Jan et al 54 are supported by other studies in the field, such as that by Rasmussen et al 55 In this study, it was demonstrated in an RCT of 300 adults with asthma that an IHCA was able to increase the patient's adherence to asthma medication, improve clinical outcomes, and improve the patient's quality of life. 55 Although effect sizes were not reported for this study, it provides supporting evidence concerning the long-term positive effects of IHCAs in the area of patient adherence to medications.…”
supporting
confidence: 74%
“…These interventions typically involve online monitoring of symptoms, health education, counseling, feedback, and prompts regarding medication use. Jan et al 54 found that an Internetbased interactive program was able to improve patient monitoring of asthma symptoms significantly and adherence with asthma medications over the course of a 12-week RCT. These increased adherence rates led to improved clinical outcomes among the intervention sample.…”
mentioning
confidence: 99%
“…Recently, a systemic review of home telemonitoring for patients with respiratory conditions, particularly when evaluated in randomised controlled trials in asthma, showed that home telemonitoring of respiratory conditions results in early identification of deteriorations in patient condition and symptom control [12][13][14][15][16][17]. In Taiwan, an internet-based asthma telemonitoring programme reportedly increased self-management skills and improved asthma outcomes, and appeared to be an effective technology for care that is well accepted by asthmatic children and their caregivers [13]. However, telephone communication is time-consuming and staff-heavy, while internet access is not always convenient.…”
mentioning
confidence: 99%
“…The comparison between the standard clinical care and the clinical trial with telemonitoring showed a potential saving by telemonitoring of €40,397.00 per patient for a 10 year period 15 . In asthma, home monitoring is more extensively studied, although only a few studies investigated the effects of home monitoring of the combination of lung function and respiratory symptoms 18 . In a recent study of our research group in 96 children with asthma, more cases of less well-controlled asthma were detected by prospective home monitoring of FEV 1 and symptoms than by a validated questionnaire during hospital visits 5 .…”
Section: Discussionmentioning
confidence: 99%